6,000 miles to freedom two boys and their flight from the Taliban - Marchetti, Stéphane 1978- (Graphic Mundi, 2022)
"A narrative account, in graphic novel format, of the traumatic experiences faced by children fleeing war and poverty in Afghanistan, as well as the isolation they often feel as refugees in the West"--
"Originally published as 9603 Kilomètres: L'Odyssée de deux enfants, Futuropolis, Paris © 2020.
Keywords: Taliban; Refugees -- Afghanistan -- Comic books, strips, etc; Refugees -- England -- Comic books, strips, etc; Refugee children -- Afghanistan -- Comic books, strips, etc; Junge -- 12 Jahre; Flucht; Afghanischer Flüchtling; Refugee children; Refugees; Afghanistan; England; Comics (Graphic works); Comic; Graphic novels